Gestational exposure to ethanol suppresses msx2 expression in developing mouse embryos - Rifas, Leonard (The National Academy of Sciences of the USA, 1997)
Ethanol acts as a teratogen in developing fetuses causing abnormalities of the brain, heart, craniofacial bones, and limb skeletal elements. To assess whether some teratogenic actions of ethanol might occur via dysregulation of msx2 expression, we examined msx2 expression in developing mouse embryos exposed to ethanol on embryonic day (E) 8 of gestation and subjected to whole mount in situ hybridization on E11–11.5 using a riboprobe for mouse msx2. Control mice exhibited expression of msx2 in developing brain, the developing limb buds and apical ectodermal ridge, the lateral and nasal processes, olfactory pit, palatal shelf of the maxilla, the eye, the lens of the eye, otic vesicle, prevertebral bodies (notochord), and endocardial cushion. Embryos exposed to ethanol in utero were significantly smaller than their normal counterparts and did not exhibit expression of msx2 in any structures. Similarly, msx2 expression, as determined by reverse transcription–PCR and Northern blot hybridization, was reduced ≈40–50% in fetal mouse calvarial osteoblastic cells exposed to 1% ethanol for 48 hr while alkaline phosphatase was increased by 2-fold and bone morphogenetic protein showed essentially no change. Transcriptional activity of the msx2 promoter was specifically suppressed by alcohol in MC3T3-E1 osteoblasts. Taken together, these data demonstrate that fetal alcohol exposure decreases msx2 expression, a known regulator of osteoblast and myoblast differentiation, and suggest that one of the “putative” mechanisms for fetal alcohol syndrome is the inhibition of msx2 expression during key developmental periods leading to developmental retardation, altered craniofacial morphogenesis, and cardiac defects.